We have x + y = x 2 − x y + y 2 , where x , y ∈ N 0 .
If there are n unordered solutions to the equation ( x 1 , y 1 ) , ( x 2 , y 2 ) , … , ( x n , y n ) , find i = 1 ∑ n ( x i + y i ) + n .
Clarification:- Unordered solution means ( p , q ) and ( q , p ) are to be counted as one solution.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice solution:-)
The expression x + y = x 2 − x y + y 2 can be written as x 2 + y 2 − x y − x − y = 0 .Now multiplied both side of the new equation by 2 and rewrite the expression as follows x 2 − 2 x y + y 2 + x 2 − 2 x + 1 + y 2 − 2 y + 1 = 2
⇒ ( x − y ) 2 + ( x − 1 ) 2 + ( y − 1 ) 2 = 2
⇒ we get three cases.
Case 1 : x − y = 0 , x = 1 , − 1 , y = 1 , − 1 here accepted solution are ( 0 , 0 ) , ( 2 , 2 )
Case 2 : x − y = 1 , − 1 , x − 1 = 0 , y − 1 = 1 , − 1 here accepted solution are ( 1 , 0 ) , ( 1 , 2 )
Case 3 : x − y = 1 , − 1 , x − 1 = 1 , − 1 , y − 1 = 0 here accepted solution are ( 0 , 1 ) , ( 2 , 1 )
but as stated in the question ( 1 , 0 ) , ( 1 , 2 ) = ( 0 , 1 ) , ( 2 , 1 ) .Hence answer would be 1 2 .
Rearranging gives x 2 + x ( − y − 1 ) + ( y 2 − y ) = 0 . Since we want to find integer roots, then quadratic discriminant (in x ) must be a square of an integer (and non-negative):
( − y − 1 ) 2 − 4 ( 1 ) ( y 2 − y ) ≥ 0 ⇔ 3 y 2 − 6 y − 1 ≤ 0 ⇔ 3 3 − 2 3 ≤ y ≤ 3 3 + 2 3 ,
so the only possible values of y are 0, 1 and 2.
Trial and error shows that ( x , y ) = ( 0 , 0 ) , ( 1 , 0 ) , ( 0 , 1 ) , ( 2 , 1 ) , ( 1 , 2 ) .
Elegant approach, Thanks.
Problem Loading...
Note Loading...
Set Loading...
In this solution, the approach is to write the equation in simple form.
x + y = x 2 − x y + y 2
⇒ ( x + y ) − x y = ( x 2 − x y + y 2 ) − x y
⇒ ( x + y ) − x y = ( x − y ) 2
⇒ − 1 + ( x + y ) − x y = ( x − y ) 2 − 1
⇒ ( x − 1 ) ( 1 − y ) = ( x − y ) 2 − 1
Now let x − 1 = a and 1 − y = b .
We find that x − y = a + b .
So the equation can be written as
a b = ( a + b ) 2 − 1
⇒ a b = a 2 + b 2 + 2 a b − 1
⇒ 1 = a 2 + b 2 + a b
Since a 2 , b 2 , and a b ≥ − 1
The only solution of above are ( a , b ) ∈ ( 0 , 1 ) , ( 1 , 0 ) , ( − 1 , 1 ) , ( 1 , − 1 )
So ( x , y ) ∈ ( 1 , 0 ) , ( 2 , 1 ) , ( 0 , 0 ) , ( 2 , 2 ) .
So the answer is ( 1 + 0 + 2 + 1 + 0 + 0 + 2 + 2 ) + 4 = 1 2 .